Gerakan Guru Menulis Buku Melalui Pelatihan Online dengan Microsoft Teams bagi Guru Se Kota Salatiga - Suranto Suranto (IKIP PGRI Bojonegoro, 2020)
The recent problems of teacher, among other, is the productivity of writing a book. There are many obstacles that teacher faces, among them, mostly, are the lack of motivation and the lack of knowledge of writing a book. The purposes of this service are: 1) to increase teacher’s motivation for writing a book, 2) to increase teacher’s skill in making a book from a research outcome, 3) to increase teacher’s skill in writing a lesson book and an enrichment book, 4) to increase teacher’s skill in writing a fiction book, 6) to increase teacher’s knowledge of publishing a book. The participants are teachers from all educational levels in Salatiga City amounted to 117 teachers. The method of activity implemented was a Microsoft Teams-aided online training. The training activity included web meeting, discussion, consultation, and assistance for 1 month. The service activity is able to motivate the teachers to write a book based on the right principles of writing a book and to produce a book in accordance with the necessity of the school where the teachers teach.